Governing corporeal movement in India during the COVID-19 pandemic - Holwitt, Pablo (Body & society, 2021)
This article explores the impact of the COVID-19 pandemic on the relationship between bodies, risk and mobility. Drawing upon ethnographic data from India, it is argued that measures taken by the Indian government to contain the spread of the pandemic link mobile bodies to the notion of risk which has profound consequences for the way in which people access and engage with public spaces in Indian cities. In this process, a new type of body ? the risky mobile body ? is produced. At the same time, these measures run into problems due to the volatile nature of knowledge about bodies and diseases that they rely on. While the mobility of the COVID-19 virus is a subject of public debate, the fluidity and open-endedness of mobile bodies makes them difficult to regulate. This mismatch between governmental logics and unknowable bodies constitutes a significant challenge for the fight against the pandemic.